Seasonality of stable isotope composition of atmospheric water input at the southern slopes of Mt. Kilimanjaro, Tanzania. Issue 22 (15th September 2017) - Otte, Insa; Detsch, Florian; Gütlein, Adrian; Scholl, Martha; Kiese, Ralf; Appelhans, Tim; Nauss, Thomas
Abstract: To understand the moisture regime at the southern slopes of Mt. Kilimanjaro, we analysed the isotopic variability of oxygen (δ 18 O) and hydrogen (δD) of rainfall, throughfall, and fog from a total of 2, 140 samples collected weekly over 2 years at 9 study sites along an elevation transect ranging from 950 to 3, 880 m above sea level. Precipitation in the Kilimanjaro tropical rainforests consists of a combination of rainfall, throughfall, and fog. We defined local meteoric water lines for all 3 precipitation types individually and the overall precipitation, δDprec  = 7.45 (±0.05) × δ 18 Oprec  + 13.61 (±0.20), n  = 2, 140, R 2  = .91, p  < .001. We investigated the precipitation‐type‐specific stable isotope composition and analysed the effects of amount, altitude, and temperature. Aggregated annual mean values revealed isotope composition of rainfall as most depleted and fog water as most enriched in heavy isotopes at the highest elevation research site. We found an altitude effect of δ 18 Orain  = −0.11‰ × 100 m −1, which varied according to precipitation type and season. The relatively weak isotope or altitude gradient may reveal 2 different moisture sources in the research area: (a) local moisture recycling and (b) regional moisture sources. Generally, the seasonality of δ 18 Orain values follows the bimodal rainfall distribution under the influences of south‐ and north‐easterly trade winds. These seasonal patterns of isotopic composition were linked to different regional moisture sources by analysing Hybrid Single Particle Lagrangian Integrated Trajectory backward trajectories. Seasonality of d excess values revealed evidence of enhanced moisture recycling after the onset of the rainy seasons. This comprehensive dataset is essential for further research using stable isotopes as a hydrological tracer of sources of precipitation that contribute to water resources of the Kilimanjaro region.